ЕКСПЕРИМЕНТАЛЬНІ ТА ЧИСЕЛЬНІ ДОСЛІДЖЕННЯ ТЕПЛОВІДДАЧІ ЗІ СКЛОПАКЕТА З ЕЛЕКТРОНАГРІВОМ ЙОГО ПОВЕРХНІ - Басок, Б.І.; Давиденко, Б.В.; Гончарук, С.М.; Павленко, А.М. (Інститут електродинаміки Національної академії наук України, 2022)
The results of experimental and theoretical studies of heat transfer processes through a two-chamber double-glazed window (4i-10-4M1-10-4i) with electric heating are presented. Electric heating was carried out on the inner surface of the inner glass by applying voltage to its low-emission coating. A thermophysical model of heat transfer through an electrically heated double-glazed window has been created. This made it possible to determine the characteristics of the thermal regime of double-glazed windows with electric heating. Verification of the created numerical model was carried out using the data of experimental studies. The obtained distributions of heat fluxes and temperatures on the outer and inner surfaces of a double-glazed window with electric heating are analyzed. References 12, figures 8.